Classroom Environment Factors Influencing Reading Among Standard Three Primary School Pupils in Kisii ,Kenya - Caroline, Oroo K. (JOOUST, 2015)
Reading is one of the most important skills for a happy, productive and successful life. Studies carried out by the Southern and Eastern African Consortium for Monitoring Educational Quality (SACMEQ) a regional research project involving 14 countries in sub-Saharan Africa, mainly to monitor learning achievement at primary school level, indicated that class three pupils' reading levels were low across many parts of Africa and Kenya as a country inclusive. Another study by Uwezo on Kenyan pupils reading competency across counties indicated that less than a third of children enrolled in grade three lack basic grade two level literacy skills in reading. Kisii South Sub-County recorded a reading percentage of 21.00%, which is below the national average of 27.2% in light of this, it can be realized that class three pupils have low reading levels. It is because of these low reading levels that the study investigated the classroom environment factors influencing reading levels among standard three primary school pupils in Kisii South Sub-County. The objectives of the study were: to find out how reading materials influenced reading levels; to establish the effects of class size on reading levels; to establish the influence of instructional strategies on reading levels and to find out the challenges that teachers face while instructing children in reading. The study was guided by Bronfenbrenner's Ecological Model (1979) Theory and Vygotsky's (1978) Zone of Proximal Development Theory. The study adopted a mixed method approach with a concurrent triangulation design. The population targeted was all the 300 class one to three teachers, 3,973 pupils, 96 head teachers, 1 Quality Assurance and Standards Officer and all the 96 primary schools. Cluster sampling and purposive sampling methods were used, to sample 90 teachers, 10 head teachers, 1 Quality Assurance and Standards Officer and 29 primary schools. Questionnaires, interview schedules and observation checklist were used to collect primary data while secondary data was collected through literature review. Reliability was ensured by test-retest method while validity was ensured by expert judgment. Quantitave data was analyzed using both descriptive statistics and inferential statistics. The data was presented using frequency tables, charts and percentages. Pearson product-moment coefficient correlation was used to establish the relationship between the variables at a=0.05 significance. On the other hand qualitative data was analyzed by thematic frame work. The study revealed that there was a very strong positive (r= .916) correlation between reading materials and reading levels. Concerning class size and reading levels, there was a strong positive (r=.754) correlation. It was also found that there was a strong positive (r =.788) correlation between reading levels and the instructional strategies. In relation to challenges that teachers faced 80.25% cited limited resources, 40.74% noted that the curriculum was inadequate, while 74.34 cited the use of complex teaching methods. Teachers used various methods to enhance reading like being friendly to learners and small group tutorials. The study recommends that teachers should enhance reading levels among learners by adopting the phonetic teaching, whereby they teach through joining sounds of letters in a word. Parents through the board of management should assist the schools in the provision of reading materials like course books and story books. The study findings are of significance to the Ministry of Education in understanding the materials necessary in class three to improve their reading levels. V
Keywords: Factors Influencing Reading Levels.; Classroom Environment Factors.